The Porous Surface Model, a Novel Experimental System for Online Quantitative Observation of Microbial Processes under Unsaturated Conditions - Dechesne, Arnaud (American Society for Microbiology (ASM), 2008)
Water is arguably the most important constituent of microbial microhabitats due to its control of physical and physiological processes critical to microbial activity. In natural environments, bacteria often live on unsaturated surfaces, in thin (micrometric) liquid films. Nevertheless, no experimental systems are available that allow real-time observation of bacterial processes in liquid films of controlled thickness. We propose a novel, inexpensive, easily operated experimental platform, termed the porous surface model (PSM) that enables quantitative real-time microscopic observations of bacterial growth and activity under controlled unsaturated conditions. Bacteria are inoculated on a porous ceramic plate, wetted by a liquid medium. The thickness of the liquid film at the surface of the plate is set by imposing suction, corresponding to soil matric potential, to the liquid medium. The utility of the PSM was demonstrated using Pseudomonas putida KT2440 tagged with gfp as a model bacterium. Single cells were inoculated at the surface of the PSM, and the rate at which colonies expanded laterally was measured for three matric potentials (−0.5, −1.2, and −3.6 kPa). The matric potential exerted significant influence on colony expansion rates, with a faster rate of spreading at −0.5 than at −1.2 or −3.6 kPa (diameter increase rate, ca. 1,000, 200, and 17 μm h(−1), respectively). These differences can be attributed to cell motility, strongly limited under the most negative matric potential. The PSM constitutes a tool uniquely adapted to study the influence of liquid film geometry on microbial processes. It should therefore contribute to uncovering mechanisms of microbial adaptation to unsaturated environments.